Cantando e escutando amores : as obras intelectuais de Dona Ivone Lara e de Leci Brandão sobre relações afetivo-sexuais - Lucianna Sousa Furtado Brito (2023)
This research aims to explore how Dona Ivone Lara’s and Leci Brandão’s intellectual works on love theorize about Black women’s shared experiences in their affective and sexual lives. We combine our perspective on Communication, which focuses on communicative interactions between subjects, to the intersectional paradigm and other contributions from Black feminist thought, elevating music as an expression of Black intellectual tradition. Among the songs composed and sung by the authors, we selected those that approach love and affective-sexual relations, listening to them alongside works from scientific research and other intellectual production about the issue, privileging Black female perspectives in order to value this epistemic position in accordance with the empirical material. The method for analyzing Dona Ivone Lara’s and Leci Brandão’s musical-poetical works approaches the conception of love and the sung communicative interactions according to three axes: 1) the lyrical subject’s elaboration, concerning the forms of subjectivation; 2) the practice of love, desire and relationships, regarding the constitution of the relationship with the loved or desired subject; 3) the position of love, desire and the relationship in society, referring to its social place and its broader political dimension. Our analysis shows that Dona Ivone Lara and Leci Brandão elaborate different conceptions of love: while the first tackles the marks of “banzo” and melancholy in love’s transience, the latter approaches the contradictions between heterosexual models and the struggle against homophobia, elevating the pleasure and truth present in homoaffective love. Both authors take the practice of love as a starting point to constitute themselves as subjects in their songs, materializing, in their artistic-political work, actions which are consistent with their professional lives. Both engage in Black female self-valuation, stating themselves as worthy of respect and the right to love and be loved. Their songs converge in the functions of offering relationship advice and establishing criteria to differentiate desirable love from unhappy relationships, singing love through life-affirming practices such as fondness, reciprocity, respect and happiness. Faith and religious beliefs emerge in different ways: although both approach love as a divine gift, in Lara’s songs the divine entity is associated with the notions of justice, reward and punishment, while in Brandão’s the sacred happiness of love is realized in its carnal, sexual fulfillment. Both challenge the romantic notion of eternal love, proposing alternatives to relationships characterized by devaluation, in which Lara treats love’s ending as natural and inevitable and Brandão advocates the search for a love that matches her own way of loving. Finally, the analysis shows that, although they do not name the oppression of race, gender and social origin in the same terms as scientific research on the subject, the songs position themselves as resistance against power structures and their impacts on Black women’s social lives, in close relation to central issues for Black feminist thought. Therefore, our method for listening and analyzing the songs allowed us to hear the silent in-between spaces that connect them to Black women’s shared experiences in their affective-sexual relationships.